2013
DOI: 10.1186/1479-5876-11-87
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sevoflurane postconditioning on cell death, inflammation and TLR expression in human endothelial cells exposed to LPS

Abstract: BackgroundSevoflurane is an anesthetic agent which also participates in protective mechanisms in sepsis, likely due to anti-inflammatory properties. A key tissue in sepsis is the endothelium, which expresses TLR2 and TLR4 receptors, known regulators of inflammatory mechanisms and potential therapeutic targets for this pathology. In this context, we explored the effect of sevoflurane postconditioning in an in vitro sepsis model.MethodsPrimary cultures of human umbilical vein endothelial cells were used for two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
31
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 44 publications
3
31
0
2
Order By: Relevance
“…Both clinical and experimental studies have shown that inhalation of SVF has beneficial effects on lung mechanics reducing airway resistance in asthmatic individuals . In addition, previous studies have shown that inhalation of SVF mitigates lipopolysaccharide‐induced epithelial cell and macrophage injury, reduces airway inflammatory infiltrates in rodents and benefits patients with acute lung injury . Given that SVF is a short‐acting drug and usually administrated repeatedly in the clinic, our findings extended previous observation.…”
Section: Discussionsupporting
confidence: 86%
“…Both clinical and experimental studies have shown that inhalation of SVF has beneficial effects on lung mechanics reducing airway resistance in asthmatic individuals . In addition, previous studies have shown that inhalation of SVF mitigates lipopolysaccharide‐induced epithelial cell and macrophage injury, reduces airway inflammatory infiltrates in rodents and benefits patients with acute lung injury . Given that SVF is a short‐acting drug and usually administrated repeatedly in the clinic, our findings extended previous observation.…”
Section: Discussionsupporting
confidence: 86%
“…Despite a general acceptance of the conclusions arising from those studies, the possible confounding role of anesthesia has not been systematically addressed. Anesthesia itself has an anti-inflammatory influence (3,10,13,17,23,29,36), which has been suggested to be mediated by sympathetic nerves (3), although other evidence shows that anesthetics can suppress inflammation by non-neural cellular mechanisms (23,36). The first aim of the present study was, therefore, to test whether the splanchnic anti-inflammatory pathway is activated in response to endotoxemia independently of anesthesia.…”
mentioning
confidence: 93%
“…Another potential mediator for the sevoflurane effect we observed is downregulation of toll-like receptor 2 and toll-like receptor 4 resulting in an attenuation of proinflammatory cytokines. 40 Although not assessed in this current study, phosphorylation of extracellular-regulated kinase in macrophages on LPS stimulation may be another sevoflurane-mediated immunomodulatory mechanism. 41 In contrast to previous studies, we found that pulmonary albumin content, 12,42 another integrity marker of the alveolocapillary barrier, was not different between propofol and sevoflurane groups.…”
Section: Discussionmentioning
confidence: 83%
“…40,41 In our study, however, we targeted a sevoflurane dose that mimics long-term sedation in the ICU. For that, 0.5 minimal alveolar concentration sevoflurane is sufficient.…”
Section: Discussionmentioning
confidence: 99%